Memperkuat Motivasi Belajar dan Pendidikan Karakter untuk Mewujudkan Generasi Unggul di Era Globalisasi - Ramita Kholifaturrohmah (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2022)
Education plays a significant role in improving a person's cognitive, emotional, and psychomotor abilities. The importance of learning motivation can encourage students to maintain learning and achieve their goals. In achieving their goals, students need to be given a good character education to become a superior generation, have character, and have noble character. For this reason, efforts are required to strengthen learning motivation and character education, one of which is through community service activities. This service activity was carried out by socializing at SD Negeri Kepunduhan 01 Tegal with 30 grade five students. The methods used include (1) Identifying Needs (2) Preparation of Materials Facilities and Infrastructure (3) Submission of Materials (4) Discussions and Questions and Answers and (5) Closing. The students gain experience by writing down their goals and reasons so that they are more motivated to continue studying to accomplish their goals. The results of the service are expected to strengthen learning motivation and character education to create a superior generation in the globalization era.